Post-traumatic seizures and antiepileptic therapy as predictors of the functional outcome in patients with traumatic brain injury - Pingue, Valeria (Sci Rep, 2021)
Post-traumatic seizures (PTS) are a common and debilitating complication of traumatic brain injury (TBI) and could have a harmful impact on the progress of patient rehabilitation. To assess the effect of PTS and relative therapy on outcome in the initial phase after TBI, during the rehabilitation process when neuroplasticity is at its highest, we retrospectively examined the clinical data of 341 adult patients undergoing rehabilitation for at least 6 months post-TBI in our neurorehabilitation unit between 2008 and 2019. We correlated through logistic regression the occurrence of seizures and use of anti-seizure medication (ASM) with neurological and functional outcomes, respectively assessed with the Glasgow Coma Scale (GCS) and the Functional Independence Measure (FIM). PTS were documented in 19.4% of patients: early PTS (EPTS) in 7.0%; late PTS (LPTS) in 9.4%; both types in 3.0%. Patients who developed EPTS had an increased risk of developing LPTS (OR = 3.90, CI 95% 1.58–9.63, p = 0.003). Patients with LPTS had a significantly higher risk of worse neurological (p < 0.0001) and rehabilitation (p < 0.05) outcome. Overall, 38.7% of patients underwent therapy with ASM; prophylactic therapy was prescribed in 24.0% of patients, of whom 14.6% subsequently developed seizures. Mortality was associated with a lower FIM and GCS score on admission but not significantly with PTS. The use of ASM was associated with a worse rehabilitation outcome, independently of the onset of epilepsy during treatment. LPTS appear to exert a negative impact on rehabilitation outcome and their occurrence is not reduced by prophylactic therapy, whereas EPTS do not influence outcome. Our findings caution against the generic use of prophylactic therapy to prevent post-traumatic epilepsy in patients with TBI.